Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1136/jech-2016-208369
|View full text |Cite
|
Sign up to set email alerts
|

Income and functional limitations among the aged in Europe: a trend analysis in 16 countries

Abstract: High-income groups are more in favour of the observed overall decline in functional limitations than deprived groups. Results point to potential income-related inequalities in compression of morbidity in the recent past in Europe.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
19
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 31 publications
5
19
1
Order By: Relevance
“…The findings of the present study are consistent with a growing body of studies from high-income countries showing that socioeconomic inequalities in health exist not only in middle age, but also in later phases of adulthood [ 16 , 17 , 18 , 19 , 20 , 21 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 ]. With regard to the dynamics of health inequalities with age, our results support previous findings from cross-sectional and longitudinal studies indicating that health inequalities continue to exist at older ages [ 18 , 19 , 27 , 31 ], but may be partially smaller than at middle age [ 18 , 25 , 32 , 33 , 34 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The findings of the present study are consistent with a growing body of studies from high-income countries showing that socioeconomic inequalities in health exist not only in middle age, but also in later phases of adulthood [ 16 , 17 , 18 , 19 , 20 , 21 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 ]. With regard to the dynamics of health inequalities with age, our results support previous findings from cross-sectional and longitudinal studies indicating that health inequalities continue to exist at older ages [ 18 , 19 , 27 , 31 ], but may be partially smaller than at middle age [ 18 , 25 , 32 , 33 , 34 ].…”
Section: Discussionsupporting
confidence: 92%
“…Although less attention has been paid to later life compared to other life phases, there has been increasing research activity into health inequalities in older populations in the last years. Studies from high-income countries show that socioeconomic differences in health, morbidity, healthcare, and mortality also exist in older age groups to the detriment of lower socioeconomic groups [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ]. Concerning the extent of health inequalities and their dynamics over the later life course, three contradictory hypotheses are discussed in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…A large study based on pooled data from 17 European countries showed that between 1990 and 2010, absolute inequalities in self-rated general health were mostly constant whereas relative inequalities increased [ 13 ]. Another analysis of large European data sets revealed that absolute and relative inequalities in functional limitations among older people increased between 2002 and 2014 [ 44 ]. Inequalities in single widespread diseases, such as diabetes [ 15 ], myocardial infarction or stroke [ 16 , 45 , 46 ], have been found to have remained relatively constant in recent decades.…”
Section: Main Textmentioning
confidence: 99%
“…Nor, for that matter, can studies pointing towards increasing inequities in health. Even evidence that the better-off segments of the older population show a compression of morbidity or increased survivorship in later life while others show an expansion or little overall change in morbidity and mortality cannot in and of itself demonstrate growing total health inequalities (Solé-Auró et al , 2015; Bor et al , 2017; von dem Knesebeck et al , 2017). The implicit assumption that over the last three decades there has been an overall ‘compression of morbidity’ in the developed economies of the world might imply less rather than more variability within the population of over 65 year olds, but the USA may prove to be an exception ( cf .…”
Section: Increasing Vulnerability: As Indexed By Health Inequalitiesmentioning
confidence: 99%